Economic empowerment of women good for all - Kingsley Ighobor (Africa Renewal, 2019)
Government staffer Souhayata Haidara enjoys talking about her life in a patriarchal society. Her career is a triumph of patience and perseverance, she tells Africa Renewal with a smile and a wink.